The “first woman in finance”: Emeritus Professor H. Y. Izan as role model in a male-dominated discipline - Chapple, Larelle (Journal of University Teaching and Learning Practice, 2022)
In University life, the first women to achieve status or leadership positions inevitably are perceived as role models to their colleagues, peers and students. Role model theory suggests that although we generally understand the meaning of terms such as “role model” or “mentor", the position of role model has several dimensions and is distinct from mentor. This case study on Professor H.Y. Izan, the first woman professor of finance in Australia and New Zealand, adopts the role model theoretical lens to examine Izan as trailblazer in the context of the eighteen women professors appointed after her during the period 1990-2021.